Clinical predictive factors for temporomandibular disorders following combined orthodontic and orthognathic surgical treatment in patients with Class III malocclusion. Issue 6 (2nd November 2017) - Antonarakis, Gregory S.; Kalberer, Nicole; Courvoisier, Delphine S.; Scolozzi, Paolo
Abstract: Objective: The aim of this study was to identify clinical factors predisposing to the development or worsening of temporomandibular disorders (TMDs) following orthodontic surgical treatment for Class III malocclusion. Methods: A retrospective cohort study was performed on 88 patients with Class III malocclusion having undergone a combined orthodontic and orthognathic surgical treatment. Temporomandibular joint and masticatory muscle examinations were available prior to treatment and one year post-operatively. Multivariate logistic regression was used to predict the development of post-operative TMDs, and linear regression was used to predict the worsening of TMDs using Helkimo indices. Results: Patients with Class III malocclusion presenting with pre-treatment anamnestic TMJ clicking (OR = 5.8; p = 0.03) and undergoing bimaxillary osteotomy procedures (OR = 18.6; p = 0.04) were more at risk for the development of TMDs. Discussion: TMDs must be evaluated, monitored, and managed with caution in patients with Class III malocclusion presenting with pre-treatment joint clicking and who are planned for bimaxillary osteotomies.